Beyond Environmentalism: The Social Dynamics of Maslahah Mursalah in Managing Local Tourism at Gosari Amusement Park (WAGOS) Indonesia - Achmad Room Fitrianto; Muhammad Zaki bin Haji Zaini; Asif Iqbal Siddiqui; Ajeng Tita Nawangsari; Hapsari Wiji Utami (KARSA Journal of Social and Islamic Culture, 2026)
This paper presents a case study of the management of Gosari Amusement Park (WAGOS) in Indonesia, focusing on the application of sustainable tourism development and the integration of the Maslahah Mursalah concept in the management of local tourist attractions. The development of WAGOS aims to transform Gosaari from an agricultural village into a tourism village and to stimulate the local economy and its surroundings. With its abundant natural resources, including limestone hills, cultural heritage sites, and fertile agricultural areas, the village possesses great potential to attract tourists. This research highlights the successful implementation of Maslahah Mursalah in developing the WAGOS Amusing Park for the communityâ€™s benefit. It highlights the importance of balancing benefits and potential harms in tourism development. Using a descriptive-qualitative approach and economic ethnography, this study examines the aspects of Maslahah Mursalah in the management of WAGOS. Following the fiqh rule of â€œDarâ€™ul Mafasid Muqaddam â€˜Ala Jalbi Masholih,â€ which prioritizes preventing harm over acquiring benefits, the paper argues that utilizing the ancient springs and limestone hills for tourism purposes brings greater advantages compared to the potential damages that occur. The management of WAGOS demonstrates fulfillment of the five elements of Maslahah Mursalah: Hifdzu Din (preserves the ideology and culture), Hifdzu Nafs (maintenance the spirit), hifdzu Aql (Upgrade human capacity), hifdzu Nasab (Keeping the humankind sustainability), and Hifdzu Maal (Preserving wealth and financial resources).